Teaching Students To Program In A Virtual Collaborative Environment (Pedagogical Cluster-Journal of Pedagogical Developments, 2024)
The article describes the model of organizing group interaction of students in developing joint projects within the framework of extracurricular programming activities using a multimedia programming environment. The author proposes a technology for organizing group interaction and provides an example of step-by-step group development.